A influência do treinamento físico em ratos espontaneamente hipertensos tratados com dexametasona: contribuição dos microRNAs - Herrera, Naiara Araújo (2020)
Hypertension (HT) is a multifactorial disease characterized by elevated and sustained blood pressure (BP), which can be primary or secondary. Dexamethasone (DEX) is a synthetic glucocorticoid and its chronic use causes hypertension. Hypertension exacerbation induced by DEX on spontaneously hypertensive rats (SHR) could increase mortality risk. Microvascular rarefaction is present in both primary and DEX-induced hypertension and it is associated with angiogenic/apoptotic pathway unbalance. More recently, microRNA has been considered important in determining the genesis of spontaneous hypertension, however, their role in DEX-induced hypertension in SHR has not been investigated. Conversely, physical training (T) has been recommended as a co-adjuvant for the HT treatment. Thus, the aim of the present study was to investigate whether physical training is able to attenuate blood pressure increase in SHR treated with DEX and whether if this effect is associated with changes in microRNA related to microcirculation . Normotensive (Wistar) and hypertensive (SHR) rats underwent 8 weeks of T on a treadmill (60% of maximum capacity, 5 days a week, 1 hour a day) or kept sedentary. During 14 days, after 8 weeks of physical training, animals were treated with DEX (50µg / kg of body weight per day, s.c.) or saline. Blood pressure measurement and spectral analysis were performed after DEX treatment. Subsequently, tibialis anterior muscle and left ventricle were removed and processed for capillary density and capillary-to-fiber ratio evaluation, as well as VEGF, AKT, p-AKT, eNOS, Bcl-2, capase-3-cleaved proteins levels and microRNA-16, 21, 126, 155, 221 and 222 expression. In Wistar rats, DEX increased blood pressure (+27%), caused an autonomic imbalance to the heart, reduced capillary density and capillary-to-fiber ratio on tibialis anterior muscle associated with VEGF, p-AKT / AKT, Bcl-2 reduction and caspase-3-cleaved increase. Training attenuated blood pressure (-10%) increase and autonomic imbalance to the heart and prevented capillary density and capillary-to-fiber ratio reduction on tibialis anterior muscle associated with microRNA 126 increase and with a better balance between VEGF, p-AKT/AKT, Bcl-2 and caspase-3-cleaved levels. In SHRs, training reduced blood pressure and increased tibialis anterior muscle and left ventricle capillary density and capillary-to-fiber ratio. Thus, exercise training attenuates hypertension induced by DEX in Wistar rats due to autonomic imbalance attenuation and microcirculation rarefaction prevention associated with microRNA 126 increase. T, per se, induced myocardium angiogenesis associated with microRNA 126 increase, regardless DEX treatment. In addition, T reduced H in SHR, regardless DEX treatment, due to autonomic balance and microcirculation improvement. DEX did not exacerbate hemodynamic and microcirculation alteration already present in SHR.